Graft copolymerization of poly(styrene-co-p-choloromethyl styrene) with methyl methacrylate and acryloylmorpholine by atom transfer radical polymerization: Graft copolymer characterization and monomer reactivity ratios - Temüz, MM; Coskun, M (Wiley, 2005)
Poly[styrene-graft-(acryloylmorpholine-co-methyl methaerylate)] graft copolymers in various compositions, poly(styrene-graft-acryloylmorpholine), and poly (styrene-graft-methyl methacrylate) were prepared by atom transfer radical polymerization with poly(styrene-co-p-chloromethylstyrene) (62/38) as the macroinitiator in the presence of CuBr/1,2-dipiperidinoethane at 130 degrees C in N,N-dimethylformamide. The graft copolymers were characterized by elemental analysis, IR, H-1 and C-13 NMR, and differential scanning calorimetry. The thermal stabilities of the graft copolymers were investigated by thermogravimetric analysis. The monomer reactivity ratios in the graft copolymerization of acryloylmorpholine (r(1)) and methyl methacrylate (r(2)) were calculated by the application of linear methods, such as the Finemann-Ross, inverted Finemann-Ross, Yezrielev-Brokhina-Roskin, Kelen-Tudos, and extended Kelen-Tudos methods, and the Mayo-Lewis method, which uses an integrated copolymer equation in a terminal model of copolymerization. r(1) was 1.13-2.11, and r(2) was 0.49-1.05, according to the various methods. The Yezrielev-Brokhina-Roskin method gave the best linearity for the experimental results, and the r(1) and r(2) values were 1.28 and 0.54, respectively. (c) 2005 Wiley Periodicals, Inc.
Keywords: atom transfer radical polymerization (ATRP); copolymerization; graft copolymers; reactivity ratios